Veterinary pilot study on focused ultrasound treatment of spontaneous canine and feline tumours: technical and feasibility assessment - Filippou, Antria; Evripidou, Nikolas; Spanoudes, Kyriakos; Damianou, Christakis A. (My University, 2025)
Focused ultrasound (FUS) is currently in the limelight of veterinary medicine as a novel treatment modality for companion animals, offering significant benefits over traditional techniques. In this study, the safety, feasibility, and efficacy of FUS for the treatment of various spontaneous canine and feline tumours was investigated.
Keywords: Ablation; Cat; Cancer; Dog; FUS; Tumour